Enhancing Privacy Measures in Healthcare within Cyber-Physical Systems through Cryptographic Solutions - Rani Bandaru, Venkata Naga; Sumalatha, M; Rafee, Shaik Mohammad; Prasadraju, Kantheti; Sri Lakshmi, M (EAI Endorsed Transactions on Scalable Information Systems, 2024)
INTRODUCTION: The foundation of cybersecurity is privacy, standardization, and interoperability—all of which are essential for compatibility, system integration, and the protection of user data. In order to better understand the complex interrelationships among privacy, standards, and interoperability in cybersecurity, this article explains their definitions, significance, difficulties, and advantages.OBJECTIVES: The purpose of this article is to examine the relationship between privacy, standards, and interoperability in cybersecurity, with a focus on how these factors might improve cybersecurity policy and protect user privacy.METHODS: This paper thoroughly examines privacy, standards, and interoperability in cybersecurity using methods from social network analysis. It combines current concepts and literature to reveal the complex processes at work.RESULTS: The results highlight how important interoperability and standardization are to bolstering cybersecurity defences and preserving user privacy. Effective communication and cooperation across a variety of technologies are facilitated by adherence to standards and compatible systems.CONCLUSION: Strong cybersecurity plans must prioritize interoperability and standardization. These steps strengthen resilience and promote coordinated incident response, which is especially important for industries like healthcare that depend on defined procedures to maintain operational security.
Keywords: Interoperability; Standardization; Cyber Threat Intelligence; Cybersecurity Framework; Integration; Healthcare Privacy; Cryptographic Solutions